PENGARUH LOKASI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA COFFEESHOP THE COFFEEBOX MANNA - Tita Risky; Taufik Bustami (UM. Bengkulu, 2023)
The purpose of this study was to determine the effect of location on customer satisfaction at Coffee Shop The Coffeebox Manna. To determine the effect of service quality on customer satisfaction at Coffee Shop The Coffeebox Manna. To determine the effect of location and service quality on customer satisfaction at Coffee Shop The Coffeebox Manna. This research is a type of quantitative research. The method used in this research is a quantitative descriptive method. Data collection techniques are interviews, observations, field studies and questionnaires. Data analysis techniques used descriptive analysis, multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing. There is an effect of location (X1) on consumer satisfaction (Y) Coffee Shop The Coffeebox Manna. There is an influence of service quality (X2) on customer satisfaction (Y) Coffee Shop The Coffeebox Manna. There is a simultaneous influence of location and service quality on purchasing decisions for Coffee Shop The Coffeebox Manna. Keywords: Location, Service Quality, Consumer Satisfaction